Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA): A Targeted Antioxidant Strategy to Counter Oxidative Stress in Retinopathy - Marco Zeppieri; Caterina Gagliano; Fabiana D’Esposito; Mutali Musa; Irene Gattazzo; Maria Sole Zanella; Federico Bernardo Rossi; Alessandro Galan; Silvia Babighian (Antioxidants)
Omega-3 fatty acids are critical components of cell membranes, including those in the retina. Specifically, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the primary omega-3 fatty acids that have been studied for their potential benefits in retinal health, preventing the progression of retinopathy. Several studies have shown that a higher intake of omega-3 fatty acids is associated with a lower risk of developing diabetic retinopathy and age-related macular degeneration (AMD). Reviewing clinical trials and observational studies that support the protective role of omega-3s in retinal disorders is essential. This comprehensive review aims to evaluate the current literature on the role of omega-3 fatty acids, exploring their mechanisms of action and anti-inflammatory, anti-angiogenic, and neuroprotective roles in the retina. Omega-3s have been shown to inhibit abnormal blood vessel growth in the retina, which is a significant factor in proliferative diabetic retinopathy and neovascular AMD. Furthermore, omega-3 fatty acids are often studied with other nutrients, such as lutein, zeaxanthin, and vitamins, for their synergistic effects on retinal health. Reviewing these combinations can help understand how omega-3s can be part of a comprehensive approach to preventing or treating retinopathies, especially in diabetic patients. This review emphasizes the preventive function of EPA and DHA in alleviating oxidative stress-related damage in retinal diseases, concentrating on their antioxidative mechanisms.